Pagsipat sa AlDub mula sa lenteng pantayong pananaw - Brugada, Kristoffer (Plaridel, 2016)
Access online through this link: https://www.plarideljournal.org/article/pagsipat-sa-aldub-mula-sa-lenteng-pantayong-pananaw